Canine Symmetrical Lupoid Onycodystrophy as latent psora expression: case report - von Ancken, Adalberto; Coelho, Cidéli de Paula (Pubvet, 2019)
Symmetrical Lupoid Onycodystrophy (SLO) is a unusual immuno-mediated pathology with idiopathic etiology that can affect canine species. Differential diagnosis includes fungal, bacterial and autoimmune dermatitis and neoplasia. Histopathology is the main diagnostic technique, although it demands on the distal phalanx amputation. There are no predispositions regarding to dog’s breeds and the age of ill dogs can be from 3 to 8 years old. Clinical management can take up to six months to show some effect and has a uncertain prognosis. Homeopathy aims to patient well-being and miasm dynamics must be comprehended in order to set a correct prognosis evaluation. This article reports a canine clinical case with physycal and behavioural disturbances which, treated by its Simillimum (high-diluted medicine chosen by the similia principle), expressed the SLO as a latent psora manifestation and reached a cure status later. Homeopathy figure out as a great option to treat this illness condition.